2011
DOI: 10.1186/1742-2094-8-124
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 in the central nervous system host response to systemic lipopolysaccharide administration

Abstract: BackgroundLipocalin 2 (Lcn2) is a bacteriostatic factor that may also modulate cellular function, however, little is known concerning the expression or role of Lcn2 in CNS inflammation. Therefore, here we investigated the regulation and possible function of Lcn2 in the CNS following peripheral lipopolysaccharide (LPS) injection in mice.MethodsA murine model for systemic endotoxemia was used in this study. Wild type or Lcn2 KO mice (both genotypes C57BL/6 strain) were given either a single or dual, staggered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
109
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 27 publications
(55 reference statements)
7
109
2
1
Order By: Relevance
“…Lcn2 is known to be a secreted protein (7), and our evidence here suggests that this secreted Lcn2 is also deposited in the parenchyma. With the exception of astrocytes, a similar cellular localization of Lcn2 mRNA and protein was found in the brain following systemic injection of lipopolysaccharide (LPS) in mice (20), suggesting that Lcn2 may play a more general role in the cellular response to infection.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Lcn2 is known to be a secreted protein (7), and our evidence here suggests that this secreted Lcn2 is also deposited in the parenchyma. With the exception of astrocytes, a similar cellular localization of Lcn2 mRNA and protein was found in the brain following systemic injection of lipopolysaccharide (LPS) in mice (20), suggesting that Lcn2 may play a more general role in the cellular response to infection.…”
Section: Discussionmentioning
confidence: 71%
“…The densities of the individual protein bands were normalized to that of the loading control (GAPDH) and the means Ϯ standard errors of the means (SEM) were calculated using Prism 4 software (GraphPad Inc., San Diego, CA, USA). The specificity of the antibody used for immunoblot analysis for Lcn2 had been confirmed previously (20).…”
Section: Animalsmentioning
confidence: 97%
See 2 more Smart Citations
“…LCN2 was also shown to play an important role in iron delivery (13,17), angiogenesis (18), febrile response (19), insulin resistance (20), and inflammation as an acute-phase protein (21). Recently, we (22) and other investigators (23)(24)(25) reported that brain glial cells express and secrete LCN2 under inflammatory conditions and that LCN2 mediates reactive astrocytosis (26). Nevertheless, the functional role of LCN2 in the CNS is far from clear.…”
mentioning
confidence: 99%